Indicators used to measure service innovation and manufacturing innovation - Fernando Henrique Taques; Manuel G. López; Leonardo Fernando Cruz Basso; Nelson Areal (Journal of Innovation & Knowledge (JIK), 2021)
Innovation can be a source of competitive advantage for companies, either through the improvement of methods and techniques capable of generating new products or services, or perfecting existing ones. Along these lines, it is particularly important to measure innovation and discuss the results associated therewith. The aim of this research is to address each of the main indicators of organizational innovation, separately discussing the advantages and disadvantages inherent to their deployment. The results entail a substantial theoretical advancement by improving measurement systems from various perspectives: products and processes, manufacturing and services, as well as input indicators, intermediaries and outputs. However, difficulties and limitations are still apparent, including the sort of distorting biases potentially affecting researcher estimates. Furthermore, multidimensional indicators provide a broader and more precise view of the innovation phenomenon at companies, because they are more comprehensive in the understanding of such phenomenon per se, unlike the one-dimensional choice, which carries constraints for discussing the real effects in the organizational context, especially in the case of services.
Keywords: O3; O32; O33; 650; Indicators; Innovation; Multidimensional; Services